2021
DOI: 10.12775/jehs.2021.11.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine synthetase expression in the brain during experimental acute liver failure (immunohistochemical study)

Abstract: The aim of the study was to determine the immunohistochemical level of glutamine synthetase (GS) expression in different brain regions in the conditions of experimental acute liver failure in rats. Materials and methods. The study was conducted in Wistar rats: 5 sham (control) animals and 10 rats with acetaminophen induced liver failure model (AILF). The immunohistochemical study of GS expression in the sensorimotor cortex, white matter, hippocampus, thalamus, caudate nucleus/putamen was carried out in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
(10 reference statements)
2
3
0
Order By: Relevance
“…МЕДИЧНІ НАУКИ ТА ГРОМАДСЬКЕ ЗДОРОВ'Я nucleus/putamen by 12th h after treatment and by 16th h -in the white matter and thalamus. This is comparable with our previous study [5], where AILF model caused upregulation of GS in the same brain regions, however, in the cortex and hippocampus in later terms. The latter suggests that AQP4 alterations in mentioned regions could precede changes in the astrocytic glutamate-glutamine shuttle and means that AQP4 elevation can be reasoned by other factors than the glutamine hyperosmolarity.…”
Section: Notes: Reliable Differences In Indicators Compared To the Co...supporting
confidence: 92%
“…МЕДИЧНІ НАУКИ ТА ГРОМАДСЬКЕ ЗДОРОВ'Я nucleus/putamen by 12th h after treatment and by 16th h -in the white matter and thalamus. This is comparable with our previous study [5], where AILF model caused upregulation of GS in the same brain regions, however, in the cortex and hippocampus in later terms. The latter suggests that AQP4 alterations in mentioned regions could precede changes in the astrocytic glutamate-glutamine shuttle and means that AQP4 elevation can be reasoned by other factors than the glutamine hyperosmolarity.…”
Section: Notes: Reliable Differences In Indicators Compared To the Co...supporting
confidence: 92%
“…SAE is characterized by the violation of the neurotransmitter tone in the nervous tissue, leading to pronounced brain dysfunction up to coma state [3]. The present study has demonstrated the dynamic increase in GS expression in the CLP-rat brains with slightly higher rates in the non-survived animals (likewise it was observed in AILF-model of the acute liver failure) [13], although the rise of expression in CLP-study was less significant than in AILF and was significant only 24 h after the procedure. The appearance of morphological signs of focal irreversible liver damage, which preceded significant increase in GS expression by 1 hour, might suppose addition of the liver failure of a certain degree to a course of sepsis with increased levels of hepatogenic toxins (presumably including ammonia) in the blood and directly in the brain parenchyma by 23 h after CLP-procedure.…”
Section: Discussionsupporting
confidence: 75%
“…Studies on GS, another principal player of astroglial metabolism and functions including reactive astrogliosis, have demonstrated in AILF-model pronounced but heterogeneous increase in GS expression in the cortex, white matter, hippocampus, thalamus and caudate/putamen 16 h after acetaminophen treatment and maximal values at 24 h [13]. The latter fact potentially could indicate brain regions more or less permeable for ammonia and other toxic agents as well as heterogeneous sensitivity of different brain regions to damage factors in conditions of ALF.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our previous study of acetaminophen-induced acute liver failure in rats have demonstrated pronounced region-specific increase in GS expression in 5 brain regions, namely the cortex, white matter, hippocampus, thalamus and caudate-putamen, which was remarked by higher protein expression in the cortex of non-survived rats. The latter result was suspected to be an evidence of the negative effect of increased brain GS on disease progression and decompensation during acute liver failure [19]. There have been already made successful therapeutic attempts to pharmacologically inhibit GS and subsequently attenuate ammonia-induced astroglial cytoskeletal alterations and cell swelling, finished by temporal brain edema relief [18].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported in earlier animal, in vitro and instrumental human studies that GS appeared to be upregulated in different brain regions in the conditions of acutely developed hyperammonemia [9,19], but not altered, downregulated or elevated in chronic forms of HE or liver disease without HE [7,9]. Given the mixed and conflicting earlier findings regarding the response of GS to acute/chronic hyperammonemia, this question still needs to be addressed.…”
mentioning
confidence: 93%